Evaluation of Some Indigenous Plant Extracts for Suppressing Bipolaris sorokiniana in Wheat Seed - Panna, Rokshana; Aminuzzaman, FM; Islam, MR; Bhuyan, MHM Borhannuddin (The Agriculturists, 2010)
Studies were conducted in the Seed Pathology Laboratory, Department of Plant Pathology, Sher-e-Bangla Agricultural University to evaluate some indigenous plant extracts on the incidence of Bipolaris sorokiniana of wheat and seed germination. Seed treated with plant extracts reduced the incidence of Bipolaris sorokiniana. The lowest incidence was counted (12.33%) in seeds treated with Burmuda grass extracts (1:2W/V). While the highest seed germination (99.60%) was recorded in seeds treated with this grass extract followed by 99.33% germination in seeds treated with Neem leaf extract (1:2W/V), 98.00% with nut sedge grass rhizome extract (1:2 W/V), 87.67% with Allamanda leaf extract (1:2W/V). Comparatively the lowest incidence of Bipolaris sorokiniana (14.00%) was observed in seeds treated with Neem leaf extracts (1:2W/V) followed by 14.50% in seeds treated with Nut sedge grass rhizome extracts (1:2W/V), Black cumin seed extracts (15.20%) and Allamanda leaf extract (24.00%).